MANAJEMEN PUBLIC RELATION DALAM MENINGKATKAN PUBLIC INTEREST PADALEMBAGA PENDIDIKAN ISLAM - Muhammad Ilyas Junaidi Addahil (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Schools and communities are two inseparable environments.School is a place for learning, and society is a place where the output of learning can be implemented. The community is expected to support and participate in developing the educational process in schools. In this case, a strategy or management is needed to involve the community in educational activities in schools. The effort to make it real is to build good relations between school managers and the community so that they work together together and comprehensively. An educational institution should try to create a positive image in the heart of the community, so that the community is able to make a decision to register their sons and daughters and participate actively in the development of these educational institutions. To realize this positive image, in addition to developing quality it also requires productive community relations activities based on clear functions, roles, and visions.The purpose of this study is to assess and obtain a general description of the role of public relations and strategies at Islamic universities in imaging institutions and the image of the institution. This study uses a case study with a qualitative approach, while the theory is symbolic interaction and organizational information.This paper offers an alternative to implementing effective public relations roles and functions and how to apply public relations vision and mission in educational institutions.